Using bilateral functional and anthropometric tests to define symmetry in cross-country skiers - Björklund, G.; Alricsson, M.; Svantesson, U. (Journal of Human Kinetics, 2017)
The aim of this study was to evaluate the symmetry of anthropometry and muscle function in cross-country skiers and their association to vertical jumping power. Twenty cross-country skiers were recruited (21.7 ± 3.8 yrs, 180.6 ± 7.6 cm, 73.2 ± 7.6 kg). Anthropometric data was obtained using an iDXA scan. VO2max was determined using the diagonal stride technique on a ski treadmill. Bilateral functional tests for the upper and lower body were the handgrip and standing heel-rise tests. Vertical jump height and power were assessed with a counter movement jump. Percent asymmetry was calculated using a symmetry index and four absolute symmetry index levels. At a group level the upper body was more asymmetrical with regard to lean muscle mass (p = 0.022, d = 0.17) and functional strength (p = 0.019, d = 0.51) than the lower body. At an individual level the expected frequencies for absolute symmetry level indexes showed the largest deviation from zero for the heel-rise test (?2 = 16.97, p = 0.001), while the leg lean mass deviated the least (?2 = 0.42, p = 0.517). No relationships were observed between absolute symmetry level indexes of the lower body and counter movement jump performance (p > 0.05). As a group the skiers display a more asymmetrical upper body than lower body regarding muscle mass and strength. Interestingly at the individual level, despite symmetrical lean leg muscle mass the heel-rise test showed the largest asymmetry. This finding indicates a mismatch in muscle function for the lower body.